MENGEMBANGKAN MINAT KEWIRAUSAHAAN DI KALANGAN REMAJA DESA NYITDAH KABUPATEN TABANAN - Nurcaya, I.N.; Sulistyawati, Eka; Jember, I.M.; Seminari, N.K.; Wirawati, N.G.P. (Buletin Udayana Mengabdi, 2017)
Adolescence is a period of time when people are intended to reveal and show their true identity. They start to prepare for their future, choosing what they are going to do in the future. However they need some education, developments and directions to get better in order to reach their dreams. By considering the need of some education, developments and directions, encourage us to do a community service which entitled “Developing Entrepreneurship’s Interests on The Adolescence of Nyitdah Village Kediri Sub-district Tabanan Regency.”. This activity targeted the adolescence or also known as “sekeha teruna – teruni” in order to develop their entrepreneurship’s interest. The amount of participants who participate in this events are 83 teenager who were chosen from 9 banjar that spread in Nyitdah Village. The events formally starts within 3 steps, which are September 30th, October 7th and 8th 2016. The community service was held by using lecture and discussion method. The participants get the lecture’s material, the making of business proposal, and filling the questionnaire as the evaluation of the events. The result of the community service, the adolescence or also known as “sekaha teruna teruni” is expected to be able digging their self-potential, and develop it into a business. For the community service’s team, this event is beneficial to apply theory and devoted themselves to the people.